Anaerobic Digestion and Biogas Production: Combine Effluent Treatment with Energy Generation in UASB Reactor as Biorefinery Annex - Mauro Berni; Ivo Dorileo; Grazielle Nathia; Tânia Forster-Carneiro; Daniel Lachos; Breno G. M. Santos (International Journal of Chemical Engineering)
The issue of residues and industrial effluents represents an unprecedented environmental challenge in terms of recovery, storage, and treatment. This work discusses the perspectives of treating effluents through anaerobic digestion as well as reporting the experience of using an upflow anaerobic sludge blanket (UASB) reactor as biorefinery annex in a pulp and paper industrial plant to be burned in the boilers. The performance of the reactors has shown to be stable under considerable variations in load and showed a significant potential in terms of biogas production. The reactors UASB treated 3600.00 m3 of effluent daily from a production of 150.00 tons. The biogas generation was 234.000 kg/year/mill, equivalent in combustible oil. The results of methane gas generated by the anaerobic system UASB (8846.00 kcal/m3) dislocate the equivalent of 650.0 kg of combustible oil (10000.00 kcal/kg) per day (or 234.000 kg/year). The production of 8846.00 Kcal/m3 of energy from biogas can make a run at industrial plant for 2 hours. This substitution can save US$ 128.700 annually (or US$ 550.0 of fuel oil/tons). The companies are invested in the use of the biogas in diesel stationary motors cycle that feed the boilers with water in case of storage electricity.